Targeting the Ubiquitin-Proteasome System in Limb-Girdle Muscular Dystrophy With CAPN3 Mutations - Lasa-Elgarresta, Jaione; Mosqueira-Martín, Laura; González-Imaz, Klaudia; Marco-Moreno, Pablo; Gerenu, Gorka; Mamchaoui, Kamel; Mouly, Vincent; López de Munain, Adolfo; Vallejo-Illarramendi, Ainara (Frontiers in Cell and Developmental Biology, 2022)
LGMDR1 is caused by mutations in the CAPN3 gene that encodes calpain 3 (CAPN3), a non-lysosomal cysteine protease necessary for proper muscle function. Our previous findings show that CAPN3 deficiency leads to reduced SERCA levels through increased protein degradation. This work investigates the potential contribution of the ubiquitin-proteasome pathway to increased SERCA degradation in LGMDR1. Consistent with our previous results, we observed that CAPN3-deficient human myotubes exhibit reduced SERCA protein levels and high cytosolic calcium concentration. Treatment with the proteasome inhibitor bortezomib (Velcade) increased SERCA2 protein levels and normalized intracellular calcium levels in CAPN3-deficient myotubes. Moreover, bortezomib was able to recover mutated CAPN3 protein in a patient carrying R289W and R546L missense mutations. We found that CAPN3 knockout mice (C3KO) presented SERCA deficits in skeletal muscle in the early stages of the disease, prior to the manifestation of muscle deficits. However, treatment with bortezomib (0.8 mg/kg every 72h) for three weeks did not rescue SERCA levels. No change in muscle proteasome activity was observed in bortezomib-treated animals, suggesting that higher bortezomib doses are needed to rescue SERCA levels in this model. Overall, our results lay the foundation for exploring inhibition of the ubiquitin-proteasome as a new therapeutic target to treat LGMDR1 patients. Moreover, patients carrying missense mutations in CAPN3 and presumably other genes may benefit from proteasome inhibition by rescuing mutant protein levels. Further studies in suitable models will be necessary to demonstrate the therapeutic efficacy of proteasome inhibition for different missense mutations.